The role of export competitiveness in driving Renminbi cross-border settlement: Micro-level evidence from China - Danlu Bu; Lin Jiang (PLoS ONE, 2025)
Cross-border trade settlement in Renminbi (RMB) is a crucial component of China’s efforts to internationalize its currency. This study develops micro-level indicators of RMB cross-border settlement to empirically investigate the role of export competitiveness in promoting the use of RMB in international trade. The findings reveal that export competitiveness significantly enhances RMB cross-border settlement, with the establishment of Free Trade Zones further amplifying this effect. Heterogeneity analysis indicates that the impact is more pronounced in firms with smaller scales, higher industry concentration, or greater operating liabilities. Moreover, the increased use of RMB in cross-border settlements, driven by export competitiveness, is associated with reduced import dependence and enhanced firm value. These results deepen the understanding of RMB internationalization from the perspective of firm-level trade activities and provide valuable empirical insights for the strategic promotion of RMB internationalization.